Speech Acts in EFL Classroom at Islamic Senior High School (MAN) 1 Sinjai - C.J., Juvrianto (Universitas Sanata Dharma, 2018)
Speech act takes a significant role in the whole process of teaching and learning process by the teacher and students. In line with this topic, this study aims to observe more about the use of speech act by the teacher and students in their interactions in EFL (English as a Foreign Language) classroom. This study shows that there are three kinds of speech acts performed by the teacher and students: locutionary act, illocutionary act and perlocutionary act. Those speech acts are supported by theories of J.L Austin who investigated and invented the use of speech act. The result of the study indicates some uses of speech act performed by the teacher and student which is elaborated into extract explaining more about the use of speech act in EFL classroom. Locutionary act performed by the teacher and students is used when they are conveying an expression without any specific intention within. On the other hand, illocutionary act is committed by them when they are communicating some expressions containing a certain intention to the listener. Perlocutionary act is performed by the teacher and students while they are conveying expressions and the listener will show a response and act as feedback to what the speaker says. Hopefully, the study will help both teachers and students in the implementation of good communication.Keywords: speech acts, teacher and student interaction, EFL classroomÂ